History and the micro‐foundations of dynamic capabilities - Suddaby, Roy; Coraiola, Diego; Harvey, Charles; Foster, William (Strategic Management Journal, 2020)
Research Summary The capacity to manage history is an important but undertheorized component of dynamic capabilities. We argue that the capacity to manage the interpretation of the past, in the present for the future, is a critical ability that informs a firm's ability to successfully enact changes needed to adapt to disruptive technology. We identify and elaborate three specific cognitive interpretations of history—history as objective fact, history as interpretive rhetoric, and history as imaginative future‐perfect thinking—and demonstrate how these different views of history can be mobilized by managers to sense, seize, and reconfigure around opportunities made available by understanding the invisible thread of technology. Managerial Summary History is typically understood to be a constraint on a manager's ability to effect change. A firm's past is assumed to create inertia in routines and structures that compromise a firm's ability to change. We show how acquiring a broader understanding of the role of history can improve a manager's ability to enact organizational change. Studying the evolution of technology over time and across products allows managers to sense opportunities created by technological change. Using different narrations of the past as continuous or disruptive can improve a manager's ability to motivate or resist change. Using the past to construct convincing scenarios of the future, managers can enroll key stakeholders in the industry to support a strategic direction that advances the firm's strategic goals.